Financial Technology and Digital Marketing to Improve Business Strategy of Micro, Small and Medium Enterprises - Maulida, Alfiatul; Tria Hatmanti Hutami, Lusia; Adi Prabowo , Adia (CV. Inara, 2024)
This community service is carried out to provide education or training related to financial technology and digital marketing as well as financial literacy for MSME actors, Karang Taruna, and young men and women who are interested in MSMEs in Kalibulus Bimomartani, Ngemplak, Sleman, D.I. Yogyakarta. The method used is online lectures and demonstrations via Zoom. Participants listen through a big screen and gather in a range. From the evaluation results after the training, data was obtained that 85% of participants experienced an increased understanding of Financial Technology, Financial Literacy, and Digital Marketing. In addition, 70% of participants reported that they had applied the techniques they had learned. This shows that this community service activity has succeeded in achieving the goals that have been set.